TourTracker in android application mobile / Nur Alia Hamizah Mohamad Rodzi - Mohamad Rodzi, Nur Alia Hamizah (2014)
Travelling is a kind of activity that people doing leisurely and relaxing. People nowadays did not only travel for business or working purpose only. Technology has become advances and a lot of development was happened concerning to the objective of the application. This paper discusses the use of Android application for the needs of small tourist group when they are travelling. Location Based Services (LBS) is a widely used method in mobile data services with the rapid development in wireless communication and location positioning technologies. In consideration of the needs of the small tourist group, TourTracker has been developed in a way to help them find their group member’s location when they are in a sudden lost. Besides that, this application also has list of landmark that can be useful during emergency such as hospital, police station, mosque and bank. TourTracker includes functionality to show the map around one of the best tourist attraction in Malaysia which is Petronas Twin Tower. It also shows the route direction to the landmark chosen. The location of group member also can be notified in this application where user may view the current location of his or her members. However this application was limited with the location around Petronas Twin Tower only. Maximum five tourists have been chosen with their latest version of Android mobile. Within the architecture, it is hope that it can bring benefits to the target users.